2019
DOI: 10.1111/jsbm.12471
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneurial Orientation, Technological Capability, and Consumer Attitude on Firm Performance: A Multi‐Theory Perspective

Abstract: Despite the maturing entrepreneurial orientation literature, limited advance has occurred in the theoretical aspect of entrepreneurial orientation-firm performance relationship, and wideranging empirical investigations are few. The authors address these concerns by testing a comprehensive model and by extending the theoretical boundary. Specifically, drawing on dynamic capability theory, core competence perspective, and consumer theories, we argue that technological capability is central for growth and financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 134 publications
4
38
1
Order By: Relevance
“…We view EO as such a resource that could help firms to sustain their operations and survive challenges. Numerous studies have confirmed this expectation that EO enhances firms performance (Adomako, 2018;Anderson & Eshima, 2013;Alvarez-Torres, Lopez-Torres, & Schiuma, 2019;Gupta & Batra, 2015;Kallmuenzer et al, 2018;Kreiser, Anderson, Kuratko, & Marino, 2019;Poudel et al, 2018;Wiklund & Shepard, 2005;Yoon & Solomon, 2017). Although, exceptions still exist, as some studies observed contrary findings (Frank, Kessler, & Fink, 2010) that EO does not necessarily translate into firms' high performance.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…We view EO as such a resource that could help firms to sustain their operations and survive challenges. Numerous studies have confirmed this expectation that EO enhances firms performance (Adomako, 2018;Anderson & Eshima, 2013;Alvarez-Torres, Lopez-Torres, & Schiuma, 2019;Gupta & Batra, 2015;Kallmuenzer et al, 2018;Kreiser, Anderson, Kuratko, & Marino, 2019;Poudel et al, 2018;Wiklund & Shepard, 2005;Yoon & Solomon, 2017). Although, exceptions still exist, as some studies observed contrary findings (Frank, Kessler, & Fink, 2010) that EO does not necessarily translate into firms' high performance.…”
Section: Introductionmentioning
confidence: 88%
“…All the scales utilised in this study were all adapted from previous researches: the Performance scale from Poudel et al (2018), the EO scale by Covin and Slevin (1989), and the Environmental Hostility scale from Miller and Friesen (1982). However, in recognition of the differences in context, slight adjustments were made in the statements of questions in some scales to suit the context of this study.…”
Section: Measurements and Scale Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It is evident that a firm's dynamic capabilities have been associated with its performance, but if such organizational and strategic routines to achieve new resource configurations are important, so too are the resources that can be marshalled. As with other authors examining born-globals [59] or entrepreneurial orientation [60], this research not only examines dynamic capabilities, but also consider the resources deployed and specifically international knowledge, which can be associated with building international networks and markets. The knowledge-based view emerged from the resource-based view [61].…”
Section: International Knowledge and Born-global Performancementioning
confidence: 99%